How to define borders between private and common land in Norway? - Hansen, Lars Ivar (Danish Journal of Archaeology, 2017)
This article focuses upon the delimitation between the separate farm units and the collectively exploited common lands (‘allmenninger’) in Southeastern Norway during Medieval times. In these commons, various kind of resources – like pastures, woodland and fisheries – were accessible for exploitation by a majority of farmers in the settlement community, but subject to more restrictions than the resources of the ‘outlying fields’ pertaining to the separate farms. While the majority of the farmers within the community preferred that the extension of the commons should be preserved for their convenience, two groups of farmers might appropriate parts of the original common land area: those cultivating farms bordering to the common area, and who might extend their separate farmland successively into the previous commonly held area, and landless people who wanted to establish new farms (‘clearances’) within the common land. The legislation was also double and ambiguous. On the one hand it stated that ‘the commons [should] stay in the way they have been before’. On the other hand it was declared that a farmer establishing a farm as a new clearing in the commons should become the King’s tenant and thus come under his protection. The processes behind the institutionalizing of boundaries between the commons and private farm properties are highlighted through an analysis of settlement development in two municipalities/parishes in Southeastern Norway.